Fractional double-phase nonlocal equation in Musielak-Orlicz Sobolev space - Tahar Bouali; Rafik Guefaifia; Salah Boulaaras (Boundary Value Problems, 2024)
Abstract In this paper, we analyze the existence of solutions to a double-phase fractional equation of the Kirchhoff type in Musielak-Orlicz Sobolev space with variable exponents. Our approach is mainly based on the sub-supersolution method and the mountain pass theorem.